Gusjigang’s Development of Comic Media to Increase Critical Thinking Ability: Empirical Study Based on Local Wisdom in Thematic Learning - Murtono; Santosa; Utaminingsih, Sri; Fardani, Much. Arsyad; Hartani, Anisa (International Journal of Psychosocial Rehabilitation, 2020)
This study aims to examine the effectiveness of Gusjigang’slocal wisdom-based comic media to improve students’ critical thinking skills. The research method used is the Research and Development (R&D) model, using the Quasi-Experimental Design and design forms using unequal control group designs. The sampling technique is purposive sampling. Data were obtained from grade 4 students of Sultan Agung Elementary School. Data obtained by observation, interviews, tests, and documentation. Data analysis techniques are quantitative and qualitative obtained from the pretest and posttest scores. The final results of the study showed that the development of Gusjigang’s local wisdom-based comic media was effective in improving students’ critical thinking skills. Increased students ’critical thinking obtained value of 5.633> 2.009 with sig <0.05 so that comic media based on local wisdom can improve students’ critical skills.